2009
DOI: 10.1002/ijc.24147
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk of cardiovascular disease in Hodgkin lymphoma survivors—Retrospective cohort analyses and a concept for prospective intervention

Abstract: Previous studies have shown increased cardiovascular mortality as late side effects in Hodgkin lymphoma (HL) patients. This study identifies stratifying risk factors for surveillance and defines concepts for a clinical feasible and noninvasive prospective protocol for intervention of cardiovascular side effects. HL patients diagnosed between 1965 and 1995 (n 5 6.946) and their first-degree relatives (FDR) were identified through the Swedish Cancer Registry and the Swedish Multigeneration Registry. For the HL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…Andersson et al [50] performed a retrospective review of Hodgkin lymphoma patients and their first-degree relatives through the Swedish Cancer Registry to identify stratifying risk factors for surveillance of cardiovascular side effects. The authors found that the risk of cardiovascular disease increased with young age at diagnosis, >10 years of followup, and a positive family history of congestive hear failure and coronary artery disease.…”
Section: Detection Of Nonmalignant Late Effects Of Treatmentmentioning
confidence: 99%
“…Andersson et al [50] performed a retrospective review of Hodgkin lymphoma patients and their first-degree relatives through the Swedish Cancer Registry to identify stratifying risk factors for surveillance of cardiovascular side effects. The authors found that the risk of cardiovascular disease increased with young age at diagnosis, >10 years of followup, and a positive family history of congestive hear failure and coronary artery disease.…”
Section: Detection Of Nonmalignant Late Effects Of Treatmentmentioning
confidence: 99%
“…24 Incidences of CHF in longterm HL survivors have been shown to be 10-fold higher for those receiving treatment before the age of 40 and at followup after 20 years. 4 The same study found these rates to be even higher in patients with a family history of heart disease. Similar to our study, the period 20 years after treatment appears to be when most cardiac events occur.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5] A large European analysis found significantly higher rates of cardiovascular mortality after childhood cancer treatment in people receiving a cumulative anthracycline dose greater than 360 mg/m 2 and radiation doses greater than 5 Gy. 5 Numerous other studies describe long-term cardiac toxicities, including myocardial infarction, decreased ventricular function, valvular disorders, and congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…At present, long-term estimates of risk, up to 20 years after therapy, are derived from large cohort studies of patients receiving predominantly EFRT. [36][37][38][39] Late effects of more modern approaches can ideally be captured in the context of the cooperative group trials that informed this review. 40,41 Meta-analysis of the studies included in this review would have increased statistical power to compare rates of late events between treatment approaches, but these trials were too clinically heterogeneous for this to be undertaken.…”
Section: Discussionmentioning
confidence: 99%